EVALUATION OF THE SENSITIVITY AND SPECIFITY OF THE TUBERCULOSIS SIGN AND SYMPTOM (TBSS) SCORE IN COMPARISON WITH CHEST RADIOGRAPHY AND RMT FOR DIAGNOSING TUBERCULOSIS AMONG BRICK KILN WORKERS - Soemarwoto, Retno Ariza; Listiandoko, Raden Dicky; Valentiene Messah,, Anse Diana; Dilangga, Pad; Didiek Herdarto, Mohammad Junus; Hendarto, Gatot Sudiro; Febrihartati, Isura (Universitas Aisyah Pringsewu, 2025)
This cross-sectional study aimed to evaluate the sensitivity and specificity of the Tuberculosis Sign and Symptom (TBSS) score in comparison to chest radiography and the Rapid Molecular Test (RMT) among brick kiln workers. The study employed a total sampling method, involving 92 participants. Data collection was conducted from February to March 2024 in a brick kiln located in Saribumi Village, Gading Rejo District, Pringsewu Regency, Lampung Province. The majority of participants were female (77.3%), while males accounted for 22.8%. The most common age range was 41–60 years, representing 48.9% of the total sample. Regarding job categories, most workers were employed in the molding section. Screening with the TBSS score and chest radiography showed a sensitivity of 0.25, a specificity of 0.93, a positive predictive value of 0.14, and a negative predictive value of 0.96. The sensitivity and specificity of the RMT compared to the TBSS score could not be assessed as all RMT results were negative for TB. This limitation may be attributed to suboptimal sputum sample quality. The study concludes that while the TBSS score demonstrates high specificity and a strong negative predictive value, the diagnostic utility of the RMT could not be evaluated due to uniformly negative results.